PENINGKATAN PENDIDIKAN KARAKTER SISWA MELALUI PERMAINAN TRADISIONAL INTING-INTING DOMPRAK PADA SISWA KELAS I SDN 1 KALANG KABUPATEN SERUYAN - Dewi Ratna Juwita; Liberti Natalia Hia; Ardimas Doni (Comm-Edu (Community Education Journal), 2026)
This study was motivated by the suboptimal character development of first-grade students at SDN 1 Kalang, Seruyan Regency, characterized by low levels of honesty, courage, cooperation, and attentiveness during the learning process. The study aimed to enhance character education through the implementation of the traditional game Inting-Inting Domprak. The method employed was Classroom Action Research (CAR), conducted over two cycles comprising planning, action implementation, observation, and reflection stages. The research subjects were all first-grade students at SDN 1 Kalang. Data were collected through observation, documentation, and field notes, then analyzed using both quantitative and qualitative descriptive methods. The results indicate that the traditional game *Inting-Inting Domprak* successfully improved student character across several aspects: honesty, intelligence, fairness, cooperation, assertiveness, imagination, ambition, courage, and attentiveness. At the class level, the percentage of students in the "Not Yet Developed" (BB) category decreased from 30.56% in Cycle I to 0% in Cycle II. Conversely, the categories of "Developed as Expected" (BSH) and "Developed Very Well" (BSB) increased, reaching a combined 94.44%. These findings demonstrate that traditional games can serve as effective learning media to foster student character through active, enjoyable, and meaningful learning experiences, while simultaneously strengthening the implementation of character education in primary schools.